2019
DOI: 10.31557/apjcp.2019.20.3.693
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Occurrence of Thyroid Nodules in Severely Obese Patients: A Case-Control Study

Abstract: Background:The association of obesity with the occurrence of thyroid nodules and thyroid cancer has been demonstrated. However, there is limited knowledge on the risk factors of thyroid nodules in in severely obese patients. The aim was to evaluate the occurrence of thyroid nodules in severely obese and nonobese patients and determine the factors associated considering sociodemographic, lifestyle, and biochemical variables.Methods:This is a case-control study of 134 adults which 67 nonobese, control group, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
3
3
0
Order By: Relevance
“…The results of this study show that gender is a non-significant risk factor for thyroid lesions, and its prevalence in women is higher than that in men, which is consistent with the previous reports [19,23]. But other studies [15][16][17] show that gender is an independent risk factor for occurrence of thyroid lesions.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of this study show that gender is a non-significant risk factor for thyroid lesions, and its prevalence in women is higher than that in men, which is consistent with the previous reports [19,23]. But other studies [15][16][17] show that gender is an independent risk factor for occurrence of thyroid lesions.…”
Section: Discussionsupporting
confidence: 91%
“…In this cross-sectional study, the prevalence of thyroid nodules in health checkup participants in Saudi Arabia was 27.2%, which is nearly similar to the study of Saeed et al [19], who found that solid nodules represent 28.3% of their study population, and also the study of Siqueira et al [23], who studied the factors associated with the occurrence of thyroid nodules in severely obese patients in Brazil and reported that the occurrence of nodules was 29.9% in their obese group. It is also consistent with the findings of Dauksiene et al [24], who studied the factors associated with thyroid nodules in Lithuanian subjects and noted that thyroid nodules represent 31.2%.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Many recently published clinical data pointed to a significant association between lower serum vitamin D levels and thyroid nodules across the globe [8][9][10][11] . Hence vitamin D deficiency is a modified risk factor [12] for thyroid nodular disease [13] , risk of cancer [14] . Many risk factors for nodular thyroid diseases have been identified for example, high blood glucose levels, elevated serum lipid levels, increased weight, abnormal thyroid hormone levels and history of hypertension [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Obesity and overweight are chronic conditions that have detrimental impacts on overall health ( 34 ). In recent years, the prevalence of both obesity and overweight has markedly risen ( 35 , 36 ). The BMI is considered a crucial indicator for quantifying body fat ( 37 39 ).…”
Section: Discussionmentioning
confidence: 99%